2017
DOI: 10.1109/tbcas.2017.2731370
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intracranial Pressure Readout Circuit for Passive Wireless LC Sensor

Abstract: We present a wide frequency range, low cost, wireless intracranial pressure monitoring system, which includes an implantable passive sensor and an external reader. The passive sensor consists of two spiral coils and transduces the pressure change to a resonant frequency shift. The external portable reader reads out the sensor's resonant frequency over a wide frequency range (35 MHz-2.7 GHz). We propose a novel circuit topology, which tracks the system's impedance and phase change at a high frequency with low-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The use and utility of µECoG is clearly ascending, as its core and supporting technologies are being refined and new applications are being imagined. Next-generation technologies could be catalyzed by the development of μECoG devices that are fully untethered from the external world and include all of the necessary electronics (i.e., data acquisition, power transmission, and communication) directly on the device [124,125,126,127]. Such developments will enable integrated neuroprosthetic and neuromodulation systems that will have the ability to function for the lifetime of the patient.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…The use and utility of µECoG is clearly ascending, as its core and supporting technologies are being refined and new applications are being imagined. Next-generation technologies could be catalyzed by the development of μECoG devices that are fully untethered from the external world and include all of the necessary electronics (i.e., data acquisition, power transmission, and communication) directly on the device [124,125,126,127]. Such developments will enable integrated neuroprosthetic and neuromodulation systems that will have the ability to function for the lifetime of the patient.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…It is demonstrated that the sensor could sense the pressure change by resonant frequency shift, as shown in Figure 12. There is a trade-off between frequency resolution and measurement time consumption (Babu & George, 2018;Wang et al, 2017). Our homemade reader spends 165 μS for one increment of frequency.…”
Section: Pcb Sensormentioning
confidence: 99%
“…The bandwidth was set to 0.05 to 150 Hz with an anti-aliasing filter of greater than -100 dB/decade for the low-pass filter [5]. The range of frequency for measurement of this physiological measurement is at low frequency in contrast to some other physiological circuitry application which can be in high frequencies [6]- [8]. The portable ECG was constructed as a daughter board for the Arduino Uno microcontroller, which was programmed to sample the signal at 750 Hz [9].…”
Section: A Overall Design Specificationsmentioning
confidence: 99%
“…The firmware code is implemented on a microcontroller. The Arduino Uno R3 was selected for this project due to its availability, wide community support and its efficiency in high-speed prototyping [6]. Fig.…”
Section: ) Arduino Firmwarementioning
confidence: 99%